Perception of engineering students about emergency remote education: a hybrid proposal - Enami, Lorena Mazia; Souza, Bruna Gonçalves de (Brazilian Journal of Production Engineering, 2023)
This article reports the perception of the students of the engineering courses offered by one of the campuses of a university, whose head office is in the North of Paraná, regarding the learning and opportunities in the modalities of face-to-face and remote teaching. To obtain the data to be analyzed, an exploratory and descriptive case study was conducted, with quantitative-qualitative approach, using as data collection technique the application of an online questionnaire. It was concluded that there is a tendency on the part of students to support a hybrid teaching proposal, since approximately 54.6% of students believe that this modality is equal or superior to face-to-face teaching. This happens, given the advantages and/or disadvantages in both types of teaching, such as more study time in face-to-face teaching and more opportunities for sources of income in emergency remote education, which can be balanced in a hybrid methodology. By comparison, 80.4% of students believe that they learn more in face-to-face teaching, against 19.6% of remote education.